2021
DOI: 10.1016/j.omto.2021.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A8 regulated by lncRNA-TUG1/miR-140-3p axis promotes bladder cancer progression and metastasis

Abstract: Bladder cancer is the ninth most diagnosed cancer in the world. This study aims to investigate the role and mechanisms of the taurine-upregulated gene 1 (TUG1)/miR-140-3p/ annexin A8 ( ANXA8 ) axis in bladder cancer. Western blotting and qRT-PCR determined the expression levels of ANXA8 , miR-140-3p, TUG1, and epithelial-mesenchymal transition (EMT) markers. RNA immunoprecipitation (RIP), luciferase assay, and RNA pull-down assay validated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…As WNT signaling activation had been found to overexpress in breast cancer, particularly in triple-negative breast cancer, the role of RSPO4 involved in GC progression remained unelucidated ( Coussy et al, 2017 ; Park et al, 2018 ). On a similar note, ANXA8 had been revealed to be upregulated in various cancers ( Gou et al, 2019 ; Ma et al, 2020 ; Yuan et al, 2021 ). The feedback loop between RA-RARA and ANXA8 fostered cancer initiation and progression ( Rossetti and Sacchi, 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…As WNT signaling activation had been found to overexpress in breast cancer, particularly in triple-negative breast cancer, the role of RSPO4 involved in GC progression remained unelucidated ( Coussy et al, 2017 ; Park et al, 2018 ). On a similar note, ANXA8 had been revealed to be upregulated in various cancers ( Gou et al, 2019 ; Ma et al, 2020 ; Yuan et al, 2021 ). The feedback loop between RA-RARA and ANXA8 fostered cancer initiation and progression ( Rossetti and Sacchi, 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…IHC was performed as described previously [ 21 ]. In brief, MM xenograft tumors were fixed in 4% formalin, followed by paraffin embedding and serial sectioning.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, TUG1 competitively interacted with miR-29a and triggered the expression of IFITM3 in HCC cells (71). TUG1 promoted tumor progression and metastasis via modulating miR-140-3p and Annexin A8 axis in bladder cancer cells (72). Zhang et al reported that TUG1 targeted miR-187-3p and TESC and modulated the NF-kappa B signaling pathway, which governed progression of pituitary adenoma (73).…”
Section: Lncrna Tug1 Regulates Fbxw7mentioning
confidence: 99%
“…In addition, TUG1 competitively interacted with miR-29a and triggered the expression of IFITM3 in HCC cells ( 71 ). TUG1 promoted tumor progression and metastasis via modulating miR-140-3p and Annexin A8 axis in bladder cancer cells ( 72 ). Zhang et al.…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%